DOCTOR I. Ya. PLATONOV: THE RES OF LIFE - Альков В. А. (World of Medicine and Biology, 2017)
In the article, the life and creative path of the well-known psychiatrist and founder of the Platonov physician Ivan Yakovlevich Platonov during the transitional period of the second half of the nineteenth and early twentieth centuries is considered. The peculiarity of the research is that the microhistorical approach, the history of everyday life and mentality are integrated in the analysis of the subject. Some aspects of this topic are poorly covered in historiography, but the availability of a sufficient source base makes it possible to clarify not only the biographical data of the person being studied, but also how he was, his aspirations and aspirations, his views on the world and his role in it. The author for the first time fills in some gaps in the biography of a psychiatrist, draws attention to his mentality, attitude to the humanization of the treatment of patients, business activity, the specifics of the work of the main brainchild Platonov - his private clinic, personnel policy, patient contingent, socio-political and scientific activity of the doctor, his connections in the medical environment. It is concluded that although I. Ya. Platonov was able to successfully fit into the system of capitalist relations, the consciousness of the entrepreneur-entrepreneur, a peasant, did not become completely bourgeois, and in his system of values, public needs took precedence over personal needs.
Keywords: Platonov; biography; the history of mentalities; history of health